Reflection spectra of etched FBGs under the influence of axial contraction and stress-induced index change - Yang, H.Z.; Lim, K.S.; Qiao, X.G.; Chong, W.Y.; Cheong, Y.K.; Lim, W.H.; Lim, W.S.; Ahmad, Harith (Optical Society of America, 2013)
We present a new theoretical model for the broadband reflection spectra of etched FBGs which includes the effects of axial contraction and stress-induced index change. The reflection spectra of the etched FBGs with several different taper profiles are simulated based on the proposed model. In our observation, decaying exponential profile produces a broadband reflection spectrum with good uniformity over the range of 1540-1560 nm. An etched FBG with similar taper profile is fabricated and the experimental result shows good agreement with the theoretical model.